in Silico Prediction of Caesalpinia sappan L. Secondary Metabolites towards PPARγ - Aliyah, Alma Nuril; Maghfiroh, Fauz Aulia El; Rahmadanita, Fathia Faza (Proceeding Annual Symposium on Hajj and Umrah Medicine, 2022)
Chemotherapy can cause mitochondrial dysfunction and oxidative stress that induces Chemotherapy-induced Peripheral Neurotherapy (CIPN) condition. Inhibition of pro-inflammatory transcription factors by PPARγ agonist can be used to develop CIPN treatment. To find potential compounds from plants, this study conducted an in silico study of the secondary metabolites of Caesalpinia sappan L. In this study, we conducted a molecular docking study of 27 secondary metabolites of Caesalpinia sappan L. using an in silico approach targeting PPARγ (PDB ID: 2PRG) using AutoDockVina software. ADMET characteristics were predicted using the SwissADME and pkCSM Online Tool. The results showed that metabolites from Caesalpinia sappan L. with the strongest affinity for PPARγ were Phanginin D, Phanginin E, Phanginin H, Phanginin A, Phanginin G, Phanginin B, Neosappanone A, and 8-Methoxybonducellin, compared to the native ligand. Therefore, that metabolites potentially to be developed as a treatment for CIPN.